Mendorong Kesadaran Hukum Prajurit Remaja TNI AL: Peran Strategis KKN Mandiri Mahasiswa - Deddi Fasmadhy Satiadharmanto; Sofyan Sofyan; Nur Sodikin; Pahala Parulian; Ayunia Heritawati; Dadah Muliansyah; Rika Nurhidayah; Rahmalia Malik (Al-Khidmah Jurnal Pengabdian Masyarakat, 2025)
Legal counseling at Pondok Dayung is considered crucial because low legal understanding can hinder the development of the cadets' character and increase the risk of behavior that deviates from established legal norms. The methods used in this program include socialization, training, and group discussions involving students as facilitators. The results of the program show a significant increase in basic legal knowledge, awareness of the importance of rules, and a more positive attitude toward the law among the adolescent cadets. This activity also contributes to strengthening the character and discipline of the cadets, which can ultimately lead to the creation of a more orderly and productive environment. In conclusion, legal counseling through the Independent Learning Campus (KKN Mandiri) Law students from Universitas Tangerang Raya plays a strategic role in cultivating legal awareness and improving the quality of human resources at Pondok Dayung.